Beyond the reach [videorecording (DVD)] - Hinchliffe, Dickon, 1967- (Roadside Attractions : Lionsgate, 2015)
"A cocky businessman and big-game hunter hires an earnest young guide to take him hunting in the Mojave Desert. Far from civilization, the unthinkable happens when another outdoorsman is mistaken for game and accidentally shot. Things take an even worse turn when the guide refuses to be drawn into the dishonest cover-up, and must now run for his life before the hunter - and the elements - do him in."--Container.